MAİN DİRECTİONS OF CREATİON OF ELECTRONİC CATALOGUES İN LBRARİES İN THE INFORMATİON SOCİETY - Guliyev, Oruj (Gênero & Direito, 2020)
The article analyzes the state and directions of the organization of electronic catalysts in the system of libraries, and shows the scientific-theoretical basis and methodology for the creation of electronic catalogues. The article also focuses on improving the efficiency of library services, the directions and principles of its improvement, and the optimal use of modern catalogue was noted. The article comparatively analyzes the methods used in the world practice and shows the methodological basis for the application of the innovations. In addition, at the modern era it outlines the automation of libraries, the creation of electronic catalogues, and in general problems of cataloguing, the role of libraries in providing access to documentary and database users who have access to various libraries around the world and in the country. The author concludes that the work done on the organization of electronic catalogues in our country contributes to the effective organization of the inquiry-information the process in the libraries of the Republic, accelerates access to the most valuable documents and facilitates world integration.